Assessing cross-species transmission of hemoplasmas at the wild-domestic felid interface in Chile using genetic and landscape variables analysis - Sacristán, I. (Sci Rep, 2019)
The co-occurrence of domestic cats (Felis silvestris catus) and wild felids in rural landscapes can facilitate pathogen transmission. However, in the relatively-isolated regions of southern South America there have been no comprehensive studies to assess disease transmission risks between domestic cats and forest-dwelling wild felids such as guigna (Leopardus guigna). We evaluated hemoplasma infection and the possibility of transmission between domestic cats and guignas by comparing spatial and phylogenetic patterns of pathogen prevalence. Blood/spleen samples were collected from 102 wild guignas and 262 co-occurring rural domestic cats across the entire distribution range of guigna in Chile. Hemoplasma infection was assessed by direct sequencing of the 16S RNA gene. Infection with hemoplasmas was common and geographically widespread across different bioclimatic areas for both species. The most common feline Mycoplasma species in guigna and domestic cats were Candidatus M. haemominutum (CMhm) (15.7% guigna; 10.3% domestic cat) and Mycoplasma haemofelis (Mhf) (9.8% guigna, 6.1% domestic cat). A previously undescribed Mycoplasma sp. sequence was found in two guignas and one cat. Continuous forest-landscapes were associated with higher hemoplasma-prevalence in guignas. Shared hemoplasma nucleotide sequence types between guigna and domestic cats were rare, suggesting that cross-species transmission between guignas and domestic cats may occur, but is probably uncommon. Ectoparasites, which have been linked with hemoplasma transmission, were not found on guignas and were infrequent on domestic cats. Our results suggest that transmission pathways vary among hemoplasma species and, contrary to our predictions, domestic cats did not appear to be the main driver of hemoplasma infection in guignas in these human-dominated landscapes.